Consistency Management in Database Systems: Review - Asatryan, Armen J. (Mathematical Problems of Computer Science, 2024)
By its definition, a database must serve as a faithful and incorruptible repository of data. Applications that consult the database expect a "warranty" that the database is supplying the correct values. This survey briefly presents the approaches of integrity constraint management in database systems. It reflects the various research activities in this field. We focus on central approaches, concepts, methods, and systems in this area.